2023
DOI: 10.1111/jnc.15793
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism in dopaminergic neurons influences light entrainment

Abstract: Dietary lipids, particularly omega‐3 polyunsaturated fatty acids, are speculated to impact behaviors linked to the dopaminergic system, such as movement and control of circadian rhythms. However, the ability to draw a direct link between dopaminergic omega‐3 fatty acid metabolism and behavioral outcomes has been limited to the use of diet‐based approaches, which are confounded by systemic effects. Here, neuronal lipid metabolism was targeted in a diet‐independent manner by manipulation of long‐chain acyl‐CoA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…ACSL6 is abundantly expressed in the testis, brain, and eyes. We and others previously demonstrated that ACSL6‐deficient mice develop male infertility and impaired brain function associated with a significant reduction of DHA‐containing lipids 11–15 . Here, we found that Acsl6 mRNA is highly expressed in the retina and is involved in the selective enrichment of di‐DHA‐ and ULC‐PUFA‐containing phospholipids, which supports normal visual function in mice.…”
Section: Introductionsupporting
confidence: 74%
“…ACSL6 is abundantly expressed in the testis, brain, and eyes. We and others previously demonstrated that ACSL6‐deficient mice develop male infertility and impaired brain function associated with a significant reduction of DHA‐containing lipids 11–15 . Here, we found that Acsl6 mRNA is highly expressed in the retina and is involved in the selective enrichment of di‐DHA‐ and ULC‐PUFA‐containing phospholipids, which supports normal visual function in mice.…”
Section: Introductionsupporting
confidence: 74%